Hukuman Pelaku Pelecehan Seksual Terhadap Anak Di Bawah Umur Dalam Perspektif Hukum Islam - Akmal, Faris, Hartanto, S.H., M.Hum, M. Junaidi, S.H., M.Ag (2016)
Sexual despising is some kind of crime that happened to a child in which adult or older childreen use a child as a sexual stimulating.one example of sexual despising is a sexual intercourse with under age child. Islam's law has not regulate what kind of punishment to assailant, meanwhile Al Quran n hadist didn't explain explicitly about what kind of punishment to suspect of sexual despising. Because it hasn't been in Al Quran or hadist yet, so the punishment given to the suspect is based on what we called ta'zir law, ta'zir punishment are related to Allah rights or humans rights and its not include in hudud or kafarat category. This experiment is about the punishment application to the swxual despising suspect especially in under age child in Islam's law. This experiment is kind of literature experiment becaise its use a literature as a material. Its use secondary data that investigate primer law, secondary law and tertiary law that connect to the problems. After all the data has been collected,its being analysed with content analysis method. The purpose of this experiment is to explain the application of dead punishment to under age assailant in Islam's law.